Redesign of rice cooker component by using an integrated boothroyd dewhurst DFA and axiomatic design - Muhammad Faizal, Alias (2007)
In the early process for product design, the methodology of Design for Assembly (DFA) and it guidelines are very useful to engineers. Design for Assembly is a set of guidelines developed to ensure that a product is designed so that it can be easily and efficiently manufactured and assembled with a minimum of effort, time and cost. Axiomatic Design, AD is an engineering design theory that provides a framework to decision-making in the designing process. It will consider the customer needs which very important in the product market today. The main objective of the project is to improve the assembly effectiveness by using integration of Boothroyd Dewhurst DFA method and Axiomatic Design techniques. Currently, rice cooker consists of 37 components, where several components are difficult to assemble. So, this project provides the framework to redesign the current product in order to reduce the difficulty of assembly. The stage of project is starting by gathering all information of the product and also determines the customer needs for the current product. After that, the current product is redesign based on the analysis of DFA and Axiomatic Design which is aimed to increase the design efficiency, reduce total assembly time and cost of the product. The result of this project shows the design efficiency is increased from 22.0 % to 33.0 %. From the case studies result, this evaluation system is able to improve the design in term of design efficiency, product time and cost.